POSSIBILITIES FOR DIAGNOSING ANTENATAL PATHOLOGY IN WOMEN POST-ASSISTED REPRODUCTIVE TECHNOLOGIES - Ibodullayeva , Z.V.; Gulammaxmudova, D.V. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Background: Placental insufficiency is observed in 29–40% of pregnancies in clinical settings, with some studies reporting rates as high as 78–91% depending on gestational age. These inconsistencies highlight the challenges in establishing accurate diagnostic criteria. Among women who conceive through assisted reproductive technologies (ART), placental dysfunction is diagnosed approximately twice as often. This condition contributes to serious intrauterine and perinatal complications. Despite its clinical significance, the mechanisms and early indicators of this pathology remain insufficiently explored, which contributes to elevated rates of stillbirth, neonatal morbidity, and mortality. Objective: To enhance the accuracy and early detection of placental insufficiency by applying advanced diagnostic techniques. Materials and Methods: A prospective study was carried out between 2014 and 2019 in two regions of the Russian Federation: the Kemerovo region (at the Road Clinical Hospital and Diagnostic Center, 2014–2017) and the Republic of Khakassia (at the Republican Perinatal Center, 2017–2019). Data analysis extended into 2020. The change in research location was due to the lead researcher’s relocation. The research targeted pregnant women who underwent comprehensive analysis of placental blood circulation to detect early signs of insufficiency.. In pregnancies resulting from assisted reproductive technology (ART), enhanced monitoring of the fetoplacental system was implemented, including ultrasound examinations and histological analysis of the placenta after delivery. Upon enrollment, each participant underwent comprehensive medical history collection, laboratory investigations, and imaging diagnostics. Results: The study included 60 pregnant women who had no underlying systemic illnesses. Of these, 40 were part of the primary group showing signs of chronic placental insufficiency, while 20 were in the control group without such symptoms. Eligibility criteria included conception via IVF, consistent monitoring by the lead author, and delivery under their supervision followed by placental histopathology. All participants completed the full research protocol. Data were documented using maternal health records and analyzed according to IAEA/WHO guidelines. The leading causes of chronic placental insufficiency were: preeclampsia (68.4%), threatened miscarriage (34.7%), a history of complicated obstetric/gynecological conditions (32.5%), isoimmune incompatibility (25.6%), gestational pyelonephritis (14.2%), and maternal anemia (13.2%). No negative incidents were observed throughout the course of the study. Conclusion: Standard second-trimester assessments, such as measuring resistance in the umbilical artery and basic fetoplacental imaging, often provide limited diagnostic value. For earlier and more accurate detection of placental insufficiency, a thorough radiological evaluation the proper functioning of the mother–placenta–fetus system plays a crucial role.